Close your eyes - Robotham, Michael, 1960- (Mulholland Books, Little, Brown and Company, 2016)
When a former student bungles the investigation of a mother-daughter double murder, clinical psychologist Joseph O'Loughlin discovers a link between the case and a series of escalating attacks.